Análise da expressão de MDR1, MRP1, MRP2 e da superfamília EGFR nos carcinomas mamários esporádicos de cadelas - Salgado, Breno Souza [UNESP] (2015)
Mammary tumors comprise the most common neoplasms in female dogs with more than half with malignat characteristics. Such tumors are usually treated using surgical mastecty, but results are frequently not satisfying. Since new therapeutical approaches are needed in canine mammary tumors, especially regarding adjuvant therapy and targeted therapy, an understanding regarding possible cellular components related to drug resistance and that work as possible targets for therapy is straightforward to achieve. Accordingly, the aim of the research described in this thesis was to study the possible role of epidermal growth factor receptor family (EGFR) and ATP-binding cassete (ABC) superfamily members in canine mammary tumors as cancer biomarkers and its relation with disease outcome in order to better characterize their pathobiology looking forward the future improve in canine mammary cancer treatment. In this study, tyrosine kinase receptors EGFR/HER1, HER2, HER3, and HER4, as well ABC transporters P-glycoprotein/MDR1, MRP1, and MRP2 were immunohistochemically evaluated and results were related with clinicopathologic characteristics and overall survival in 43 tumors. Expression of all family members and simultaneous expression of EGFR/HER1, HER2, and HER4 were related with a poor disease outcome. P-glycoprotein and MRP1 expression showed to be related with clinicopathologic features and MRP1 was characterized as a independent prognostic indicator in such tumors. In summary, this thesis provides new information about EGFR family expression in canine mammary tumors and associates ABC transporters with a poor disease outcome, consequently suggesting that they may also be related to prognosis in patients with mammary cancer